The Impact of Stock Overvealuation on Abnormal Stock Returns and their Volatility over Time - علی قاسمی; محمد رضا نیک بخت (مطالعات تجربی حسابداری مالی, 2015)
This study examines the impact of stock overvaluation on abnormal stock returns and their volatility over time in listed companies of Tehran Stock Exchange. To measure stock overvaluation, Rhodes-Kropf et al (2005) research and to measure abnormal stock returns and rheir volatility over time, the Fama and French (1995) three-factor model has been used. The population of this study, included of 64 companies in listed companies of Tehran Stock Exchange that through sampling removed & systematically, and ten-year period from 2005 to 2014 for the statistical & necessary tested on them. The results by using multivariate linear regression using panel data and fixed effects approachsuggest that stock overvaluation has a positive and significant impact on abnormal stock returns and volatility of in over time. In other words, by increasing the stock over evaluation over time, abnormal stock returns and their volatility significantly increased. It is recommended to business executives by providing the necessary background for a realistic evaluation of the stock, the necessary fields in order to reduce the abnormal returns of stocks and them volatility to bring over time.